The Importance of the Orbital Parameters for the Indian Summer Monsoon During the Mid-Holocene, as Deciphered From Atmospheric Model Experiments - Tejavath, Charan Teja; Ashok, Karumuri; Chakraborty, Supriyo (Frontiers in Earth Science, 2021)
Proxy and modeling-based studies suggest multi-scale temporal variability in the Indian summer monsoon (ISM). In this study, using the CESM1 atmospheric general circulation model, we carried-out multiple ensemble AGCM simulations for the Mid-Holocene (MH; ≈ 6 kyr BP), Medieval Warm Period (MWP; ≈ 1 kyr BP), Little Ice Age (LIA; ≈ 0.35 kyr BP), and Historical (HS; ≈ CE 2000) periods. We used the PMIP3/CMIP5 boundary conditions for this purpose. Our simulations indicate that the ISM during the MH was stronger compared to HS and the rainfall is higher, in agreement with several proxy studies. The experiments also suggest that the MWP received higher ISM rainfall (ISMR) relative to the LIA, in agreement with the results from the PMIP3 models. Relatively northward migration of the ITCZ over the Indian region and strengthening of the neighboring subtropical high over the northwestern Pacific, both associated with stronger insolation associated with the obliquity and precision during the MH, seem to be the main reason for a wetter Indian summer monsoon during the MH.